Enhancing Environmental Quality: Investigating the Impact of Hydropower Energy Consumption on CO2 Emissions in Indonesia - Maulidar, Putri; Fadila, Sintia; Hafizah, Iffah; Zikra, Naswatun; Idroes, Ghalieb Mutig (Ekonomikalia Journal of Economics, 2024)
Achieving sustainable environmental quality has become a critical global issue, necessitating the reduction of carbon dioxide (CO2) emissions and greenhouse gas (GHG) emissions to mitigate environmental pollution. Hydropower energy has the potential to play a significant role in this effort by providing a clean, renewable energy source that can help reduce reliance on fossil fuels and decrease CO2 emissions. This study examines the dynamic impact of hydropower energy consumption, economic growth, capital, and labor on Indonesia's CO2 emissions from 1990 to 2020. Applying the Autoregressive Distributed Lag (ARDL) method, the findings demonstrate that hydropower energy consumption has a negative effect on CO2 emissions in both the short and long term, indicating that increasing hydropower energy consumption leads to a reduction in CO2 emissions. Conversely, labor exhibits a positive influence on CO2 emissions in both the short and long term, suggesting that a rise in labor contributes to higher levels of CO2 emissions in Indonesia. Furthermore, the Granger causality analysis reveals a bidirectional relationship between CO2 emissions and hydropower energy consumption. The robustness of ARDL results is confirmed through additional tests using Fully-Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), and Canonical Cointegrating Regressions (CCR) methods. The findings underscore the importance of promoting sustainable hydropower energy for effective environmental management in Indonesia. Policymakers should prioritize investments in sustainable hydropower infrastructure, encourage the adoption of energy-efficient technologies, and develop a skilled workforce to mitigate the environmental impact of increased labor force participation.